Internet Platform Employment in China : Legal Challenges and Implications for Gig Workers through the Lens of Court Decisions - Wang, Tianyu; Cooke, Fang (Relations industrielles / Industrial Relations, 2021)
SummaryResearch Objective and QuestionsWe aimed to examine court rulings on disputes between network platforms and labour providers in order to understand the nature of the employment relations and the broader consequences for society as a whole. We addressed two questions :What is the attitude and role of the courts in resolving disputes between Internet network platforms and labour providers in China within a civil law system ?What are the prospects that legal innovations will improve protection for platform labour providers who fall outside the scope of labour law, in order to counter the unregulated expansion of digital capitalism at the expense of the under-/unprotected ?MethodologyWe primarily used secondary data, namely 102 publicly available Court decisions from 2014 to 2019. The case decision reports were downloaded from the Supreme People’s Court “Network of Court Decision Papers.”ResultsDisputes occurred mainly in cities that have the most developed platforms and an independent worker model of employment. They mainly involved network platforms that provide such services as driving, food delivery and courier services. All of the disputes involved road accidents, and over half occurred in Beijing and Shanghai—two leading cities in China that have dense populations. Dispute cases rose sharply, peaked in 2017, started to drop in 2018 and fell even more in 2019. The disputes seem to have educated people on both sides, with the result that more precautions are being taken.ContributionsOur study makes three contributions. First, we identified three types of platform employment in China, the motives of the platforms in their choice of labour utilization and the legal implications in terms of labour and third-party protection. Second, we examined the attitude and role of the courts in judging disputes between network platforms and labour providers within legal constraints. Third, we propose that socialization of contract service should be central to platform employment.